Sosialisasi Perpajakan Memoderasi Pengaruh Kewajiban Moral dan Kualitas Pelayanan pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Gustiari, Luh Ayu; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi, 2018)
Taxpayer compliance is the effort of the taxpayer in fulfilling his tax obligations to increase tax revenue. The purpose of this study is to determine the effect of taxation socialization as a moderator of the influence of moral obligations and service quality on compliance of motor vehicle taxpayer s. Population used in this research is all of motor vehicle t axpayer registered and active in SAMSAT Denpasar. Th is research used nonprobability sampling with purposive sampling technique. Methods of data collection through questionnaires that have been distributed to 100 respondents and then the data were analyzed using multiple linear regression analysis techniques and moderated regression analysis . The results of this study is show that moral obligation, quality of service have a positive effect on the compliance of motor vehicle taxpayers , socialization of taxation strengthen the influence of service quaity on compliance of motor vehicle taxpayers , and socialization of taxation is not proven to moderate the influence of moral obligations on compliance of motor vehicle taxpayers . Keywords: taxpayers compliance, moral obligation, quality of services, and socialization.